MUC1 peptide vaccine mediated antitumor activity in non-small cell lung cancer - Sharma, Sherven (2011)
Lung cancer is the most common cause of cancer mortality worldwide for both men and women, causing approximately 1.2 million deaths per year. With the existing therapeutic efforts, the long-term survival for lung cancer patients remains low with only 15% surviving for 5 years following diagnosis. Therefore, new therapeutic strategies are needed. One such approach is the development of immune therapy for lung cancer. Immune approaches for lung cancer remain attractive because although surgery, chemotherapy and radiotherapy alone or in combination have response rates in all histological types of lung cancer, relapse is frequent. Immunologic targeting of lung cancer has the potential for nontoxic and specific therapy. Strategies that harness the immune system to react against tumors can be integrated with existing forms of therapy for optimal responses toward this devastating disease.